The role of big data in changing the scope of the modern Indian banking sector - Mukesh Kumar Mishra (ResearchGate, 2023)
Big data has become a crucial asset for the modern Indian banking sector, driving innovation, improving decision-making, and ultimately enhancing the overall banking experience for customers. As technology continues to advance, the role of big data in banking is likely to evolve, bringing about further improvements in efficiency, security, and customer-centric services. The integration of big data analytics in banking operations has brought about several changes, enhancing efficiency, customer experience, risk management, and decision-making processes. This paper explores the transformative role of big data as a service (BDaaS) and its applications in the Indian banking sector. The study highlights how BDaaS serves as a robust and innovative instrument, contributing significantly to the identification and prevention of security issues and fraudulent behavior within the industry. The experimental results suggest that deploying big data technology is crucial for various aspects, particularly in handling financial risks and managing operational workflows within the banking sector.
Keywords: G1; G21; O33; G28; 330; Big Data; Banking System